Synthesis and metal binding properties of N-alkylcarboxyspiropyrans - Perry, Alexis; Kousseff, Christina J. (Beilstein Journal of Organic Chemistry, 2017)
Spiropyrans bearing an N-alkylcarboxylate tether are a common structure in dynamic, photoactive materials and serve as colourimetric/fluorimetric cation receptors. In this study, we describe an efficient synthesis of spiropyrans with 2–12 carbon atom alkylcarboxylate substituents, and a systematic analysis of their interactions with metal cations using 1H NMR and UV-visible spectroscopy. All N-alkylcarboxyspiropyrans in this study displayed a strong preference for binding divalent metal cations and a modest increase in M2+ binding affinity correlated with increased alkycarboxylate tether length.
Keywords: carboxylate ligand; merocyanine; metal binding; photochromism; spiropyran